(3GdYHGH aj TQM CHjGJ GdBOGHs - (3TQa GdOjf MSfs; (3GHf TeS GdNdGaI , LYaQ Hf eMeO Hf CHh GdaVd (B((3TeS GdNdGag(B) (3eNJGQ GdGaVdj, eLO Gdedc,J (B622 (3g` s ((3UdGM GdOjf Hf CMeO Hf UdGM s)
(3ChdgG (B:s
(3aGfj deG hbaJ Ydi cJGH GdBOGH JCdja SfGA Gdedc LYaQ Hf TeS GdNdGaI s
(3BNQgG (B:s
(3hefgG bhd GdeJfHj(B: (3aoQH cFjH djS JfOi Lahfg hoQH cKjQ GdOeY ZjQ cFjH Je GdcJGH Hef Gddg Gdhdj GdhgGH s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B128 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B149s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B26 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B766s
Keywords: (3GdCOHs